2018
DOI: 10.1155/2018/6346734
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect and Mechanism of Arctium lappa Extract on NLRP3 Inflammasome Activation

Abstract: Arctium lappa (A. lappa), Compositae, is considered a potential source of nutrition and is used as a traditional medicine in East Asian countries for centuries. Although several studies have shown its biological activities as an anti-inflammatory agent, there have been no reports on A. lappa with regard to regulatory role in inflammasome activation. The purpose of this study was to investigate the inhibitory effects of A. lappa extract (ALE) on NLRP3 inflammasome activation and explore the underlying mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 45 publications
(49 reference statements)
1
17
0
Order By: Relevance
“…Although several biological properties of A. lappa have been described [1], our study is the first to describe its action as complement inhibitor. This immunomodulatory activity of A. lappa extracts corroborates with the anti-inflammatory actions previously reported such as activation of antioxidant enzymes and scavenging of free radicals [19,21], inhibition of inhibition of inducible nitric oxide synthase (iNOS) pathway [22], suppression of pro-inflammatory cytokine expression [22], inhibition of the nuclear factor-kappa B [23], and inhibition of NOD-like receptor pyrin domain-containing-3 (NLRP3) inflammasome activation [5].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Although several biological properties of A. lappa have been described [1], our study is the first to describe its action as complement inhibitor. This immunomodulatory activity of A. lappa extracts corroborates with the anti-inflammatory actions previously reported such as activation of antioxidant enzymes and scavenging of free radicals [19,21], inhibition of inhibition of inducible nitric oxide synthase (iNOS) pathway [22], suppression of pro-inflammatory cytokine expression [22], inhibition of the nuclear factor-kappa B [23], and inhibition of NOD-like receptor pyrin domain-containing-3 (NLRP3) inflammasome activation [5].…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, Burdock has been used in traditional Chinese medicine and in alternative ther-apies in Europe, Asia, and North and South America [1,2]. Several parts of this medicinal herb, including, roots, leaves, seeds, and fruits, have different scientifically proven biological activities such as hypolipidemic [4], anti-inflammatory [5,6], antifungal [6], and antitumor properties [7]. In addition, Holetz et al demonstrated that the extracts of A. lappa from plants collected in southern Brazil presented bactericidal activity against Gram-positive and Gramnegative bacteria [2].…”
Section: Introductionmentioning
confidence: 99%
“…The positive effects of IF on brain health in pre-clinical studies comprised improved cognitive function with reduced oxidative stress during middle age when IF was commenced in young adult age [86] and delayed occurrence of age-related brain impairments [87]. Moreover, in models of ischemic stroke, IF modulated forebrain neurogenesis, autophagy, and apoptosis, attenuated inflammasome activity, suppressed detrimental genetic pathways, and improved recovery [88][89][90]. IF was also found to be efficient for reducing neuroinflammation and preserving cognitive function after lipopolysaccharide administration, an animal model of systemic bacterial infection [91,92].…”
Section: Intermittent Fasting As a Means To Combat Agingmentioning
confidence: 99%
“…ALE significantly reduced the LPS-induced increase of plasma IL-1β in the mouse peritonitis model [3]. Arctigenin (ATG) was able to ameliorate LPS-induced inflammation through accumulating myeloidderived suppressor cells (MDSCs), especially granulocytic MDSCs, and enhancing the immunosuppressive function of MDSCs in vivo and in vitro [4].…”
Section: Gunamentioning
confidence: 99%
“…Crude polysaccharide fraction (SAA) resulting from aqueous extraction of AL leaves showed a dosedependent anti-edematogenic activity on carrageenan-induced paw edema, which persisted for up to 48 h [6]. Arctiidilactone (1), a novel rare butyrolactone lignan with a 6-carboxyl-2-pyrone moiety and 11 new butyrolactone lignans (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) were isolated from the fruits of AL L., exhibited stronger anti-inflammatory effects than the positive control curcumin [7]. Upregulated NFE2L2.…”
Section: Gunamentioning
confidence: 99%